Measurement of neutrino oscillations with IceCube-DeepCore - Vehring, Markus (RWTH Aachen University, 2017)
RWTH Aachen University, Diss., 2017; Aachen, 1 Online-Ressource (xv, 179 Seiten) : Illustrationen, Diagramme (2017). = RWTH Aachen University, Diss., 2017 : Neutrino oscillations are an active topic of research with several yet unresolved issues. Neutrino oscillations occur due to a mixing of flavor- and mass-states which results in a varying probability to measure a distinct neutrino flavor. This effect is dependent on the propagation length and energy of the neutrino. For a detector measuring muon neutrinos produced in the Earth’s atmosphere, the oscillation is visible as an energy and zenith dependent deficit in muon-neutrino events compared to the hypothesis of no neutrino oscillation.The IceCube Neutrino Observatory is a neutrino detector located at the geographical South Pole. Its extension DeepCore enables the detection of muon neutrinos of low-energy. With an energy threshold as low as 10 GeV DeepCore triggers to about 150 000 atmospheric muon neutrino events each year. This enables the measurement of the oscillation of muon neutrinos into other flavors.In a recent analysis using three years of IceCube data from 2011 to 2014, a sensitivity comparable to dedicated neutrino oscillation experiments was achieved. This work extends that analysis by including another year of data that was measured between 2010 and 2011. The live time of the analysis is increased from 953 to 1266 days. This permits an improvement in sensitivity. Also it is explored, how the analysis can be improved further. : Published by Aachen